2020
DOI: 10.1186/s12879-020-05337-4
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-orbital mucormycosis due to Apophysomyces ossiformis in a patient with diabetes mellitus: a case report

Abstract: Background: The most common aetiological agents of mucormycosis are Rhizopus, Mucor, Apophysomyces and Lichtheimia. Apophysomyces is comparatively rare, as it has been reported in less than 3% of mucormycosis cases. The genus Apophysomyces includes six species, and only A. elegans, A. mexicanus, A. variabilis and A. ossiformis have been reported to cause infections in both immunocompetent and immunocompromised patients. Case presentation: We present a case of a 46-year-old male patient with bilateral blepharoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…with cases of CM, mainly after trauma or skin injuries [4,[37][38][39]. The genus Apophysomyces includes six species, but only A. elegans, A. mexicanus, A. variabilis, and A. ossiformis have been reported as causing infection in humans in both immunocompetent and immunocompromised patients [40]. Infections caused by this genus are rare, with less than 3% of all MM cases worldwide [40].…”
Section: Discussionmentioning
confidence: 99%
“…with cases of CM, mainly after trauma or skin injuries [4,[37][38][39]. The genus Apophysomyces includes six species, but only A. elegans, A. mexicanus, A. variabilis, and A. ossiformis have been reported as causing infection in humans in both immunocompetent and immunocompromised patients [40]. Infections caused by this genus are rare, with less than 3% of all MM cases worldwide [40].…”
Section: Discussionmentioning
confidence: 99%
“…At least four species, A. elegans, A. mexicanus A. Bonifaz et al, A. ossiforms E. Álvarez et al and A. variabilis E. Álvarez et al, are reported to cause mucormycosis (Chakrabarti et al 2010, Guarro et al 2011, Bonifaz et al 2014, Khuna et al 2019, Martínez-Herrera et al 2020. Apophysomyces species are the second common agents of mucormycosis in India (Chander et al 2021).…”
Section: Actinomucormentioning
confidence: 99%
“…Imaging investigations aid in determining the amount of tissue invasion. Mucosal thickness, sinusitis, and bone degeneration in the nasal septa, orbit, maxilla, and mandible can all be seen on CT and MRI scans of paranasal sinus mucormycosis [13,14].…”
Section: Rhino-orbital-cerebral Mucormycosismentioning
confidence: 99%